Assessing the Relationship of Psychological Sport Readiness, Single-leg Vertical Jump, and Non-Sagittal Single-Leg Hops to Quadriceps Strength After Anterior Cruciate Ligament Reconstruction - Paul Kuwik; Erin Florkiewicz; Timothy Benedict; John Mason; Jamie Morris; Michael Crowell (International Journal of Sports Physical Therapy)
# Background